Storytelling as a teaching strategy in the English language classroom in Iceland - Patience Adjahoe Karlsson 1974- (2012)
This thesis represents the final academic work required for the award of a Masters Degree in Education in the Teaching and Learning of Foreign languages, and is equal to 30 ECT. I must proudly say that this is the final work for my M.Ed. studies at the University of Iceland, School of Education. I set to find out how storytelling can be adapted in English language classroom in lower secondary schools in Iceland, in order to enhance communicative language teaching for two language foci, writing and speaking. This thesis takes sources from existing literature, personal experiences and a classroom-based study aimed at discovering how storytelling can be adapted in the ninth and tenth grade to help achieve the goals of the National Curriculum (2007) of Iceland in regards to English language teaching, Communicative Language Teaching (CLT), and specifically, to improve students’ skills in writing and speaking. My findings are based on action research design targeted at exploring the benefits of storytelling as a teaching strategy. I used oral storytelling approach to develop writing and speaking skills in a ninth and tenth-grade class in a compulsory school in Iceland. The study was carried out over six weeks, twice a week with eighty minutes used for each lesson. Activities involved in the study were: a) Oral story telling sessions by teacher; b) Writing of story outlines through prompts by students; c) Engaging peers in discussing story outlines and deriving feedback; d) Writing draft stories for feedback; e) Submitting final stories for feedback and assessment; f) Writing stories in a group; and g) Presenting stories in groups. A further step-by-step guide to group storytelling in the classroom, and to writing stories, are given and might be useful to any teacher who wants to try this powerful tool. Underlying theories are analysed, and implications for practice are discussed.